STUDI PERANCANGAN COMBINATION TOOL AIR VENT NON-CYLINDER DENGAN METODE VDI 2222 - Riona Ihsan Media (Universitas Mercu Buana, 2017)
Air vent non-cylinder is one of the products used as a stack exhaust air flow from inside to the outside of factory building and office. This product was originally created using two process tools i.e for cutting and forming separately. Many parameters must be set so that it is ineffective and efficient. This study aims to produce the concept of combination tool design which is a tool for making products using sheet metal by combining cutting and forming a one-time process. Variations of alternative concepts and process stages are made then assessed based on several factors to get the concept selected in the design process based on VDI 2222 method. From the design process is produced the concept of combination tool design with dimensions of 1012 mm x 826 mm x 516 mm and total combination style 97.5 tons.